Association of chronotype and depression symptoms in Chinese infertile population undergoing assisted reproductive technology - Jiang, Fei; Jia, Yuedi; Song, Xiaohuan; Zhu, Mengli; Wang, Xin; Luo, Guiying; Wang, Jieyu; Xu, Qianhua; Wang, Danni (Frontiers in Psychology, 2025)
ObjectiveTo evaluate the association between chronotype and depression symptoms in a group of individuals experiencing infertility and undergoing assisted reproductive technologies.MethodsThis cross-sectional study evaluated the eligibility of 1,022 infertile patients who underwent ovulation induction treatment at the First Affiliated Hospital of Anhui Medical University Reproductive Medicine Center in China between August and October 2022. We obtained socio-demographic information by inviting patients who were experiencing infertility to fill out questionnaires. Furthermore, we evaluated the participants’ chronotypes using the reduced Morningness-Eveningness Questionnaire (rMEQ). Depression symptoms were evaluated using the validated Patient Health Questionnaire-9 (PHQ-9) and were expressed as PHQ-9 scores.ResultsThe participants were classified into evening, intermediate, and morning chronotypes, accounting for 9, 68, and 22% of the total, respectively. There were considerable variations in levels of depression symptoms based on chronotype. Patients with morning chronotype had lower odds of depression symptoms (odds ratios = 0.32, 95% confidence intervals: 0.18–0.57), as did those with intermediate chronotype (odds ratios = 0.47, 95% confidence intervals: 0.28–0.77), compared to individuals with evening chronotype. Furthermore, there were no significant partner effects of chronotype on depression symptoms in male and female dyads (p > 0.05 for both).ConclusionThe results indicated a significant association between individuals who have morning and intermediate chronotypes and a reduced likelihood of experiencing depressed symptoms. Further studies are required to assess the partner effect of chronotypes on depression symptoms.